2018
DOI: 10.4103/jcd.jcd_61_18
|View full text |Cite
|
Sign up to set email alerts
|

Concealment effect of resin infiltration on incisor of Grade I molar incisor hypomineralization patients: An in vivo study

Abstract: Context:Molar incisor hypomineralization (MIH) is a commonly occurring esthetic setback among patients. Depending on the graveness of the lesion, esthetics of MIH can be improved by treatments such as enamel microabrasion, bleaching, composite resin bonding, and the combination of some or all of these techniques.Aim:The aim of this study is to evaluate the esthetic results of resin infiltration treatment on incisors with Grade I molar incisor MIH.Materials and Methods:A total of 22incisor lesions with MIH were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 23 publications
1
17
0
3
Order By: Relevance
“…Case Reports in Dentistry Once infiltrated, white spot lesions take on the appearance of the surrounding healthy enamel [11,15,16]. In this case report, the resin infiltration technique was applied to the maxillary central and lateral incisors giving an aesthetically satisfactory result, in accordance with the finding of previous studies [8].…”
supporting
confidence: 74%
See 2 more Smart Citations
“…Case Reports in Dentistry Once infiltrated, white spot lesions take on the appearance of the surrounding healthy enamel [11,15,16]. In this case report, the resin infiltration technique was applied to the maxillary central and lateral incisors giving an aesthetically satisfactory result, in accordance with the finding of previous studies [8].…”
supporting
confidence: 74%
“…The characteristic feature of MIH is the clear demarcation between the affected and sound enamels [9]. The incisor defects are usually without loss of enamel substance and are generally less serious than those seen in molars due to the absence of chewing forces [11]. The risk of defects to the upper incisors appears to increase with an increasing number of affected FPMs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CIE LAB was developed by the Commission Internationale de I'Eclairge in 1931. A color difference (ΔE) between two objects can be calculated as the Euclidean distance between two coordinates (before and after) in the color space according to the following equation:[ 16 ]…”
Section: Discussionmentioning
confidence: 99%
“…The infiltration of the resin owing to its low viscosity into the voids of enamel has been shown in many in vitro studies. Eckstein et al 29 in their study showed that infiltrant material's concealment effect on WSL had no statistically significant or clinically relevant additional color or lightness alterations between 6 and 12 months after infiltration.In the study by Bhandari et al 30 a 6-month follow-up was done and a reduction in the whiteness of white spot and also change in total color were noted only after treatment and 6 months after treatment, following resin infiltration. This study shows that resin infiltration shows immediate results and also it shows further improvement overtime.Similar results were observed by Cohen-Carneiro et al 31 who showed that lesions infiltrated with icon had good colour matching.…”
Section: Molar-incisor Hypomineralisationmentioning
confidence: 99%